Evaluating construction defect mobile application using think aloud / Zan Azma Nasruddin ... [et al.] - Nasruddin, Zan Azma; Markom, Azleen; Abdul Aziz, Maslina; Hamzah, Pa'ezah (Universiti Teknologi MARA Press (Penerbit UiTM), 2018)
Construction Defect mobile application (app) is used by Ministry of Defense's Construction Defect Inspection Team to help the team in recording construction defect. However, the mobile app has never been evaluated formally to identify any usability problems. The objectives of this study are to identify usability problems of Construction Defect mobile app using think aloud and to recommend design improvement of Construction Defect mobile app based on the identified usability problems. The think aloud study involved 15 participants. During the evaluation, every participant carried out the given tasks and gave his impressions as he went along the tasks. Three usability problems were identified. Some recommendations have been proposed to improve the design of Construction Defect mobile app. As for the future work, the study may be conducted using different usability evaluation technique.